2019
DOI: 10.21614/chirurgia.114.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-up Results of Surgical Management of Chronic Pancreatitis

Abstract: Context: Pancreatita cronică este o pierdere progresivă a funcţiei pancreatice exocrine şi endocrine. Intervenţiile chirurgicale sunt necesare în cazurile de durere insuportabilă, obstrucţie biliară sau intestinală, complicaţii cauzate de pseudochisturi sau fistule pancreatice. Obiectiv: Evaluarea rezultatelor managementului chirurgical al pancreatitei cronice, într-o monitorizare pe termen lung. Metode: Am urmărit pacienţii care au suferit o intervenţie chirurgicală pentru pancreatită cronică, în perioada 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several studies confirmed that pain is the most important single contributor in QoL decrease. With higher stages of CP, the pain is more intense, and therefore the QoL is worse [11][12][13]15 . In addition to chronic pain, malnutrition poses an additional significant factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies confirmed that pain is the most important single contributor in QoL decrease. With higher stages of CP, the pain is more intense, and therefore the QoL is worse [11][12][13]15 . In addition to chronic pain, malnutrition poses an additional significant factor.…”
Section: Introductionmentioning
confidence: 99%
“…Based on published data, surgical or endoscopic approach in the treatment of CP patients efficiently decreases symptoms including pain, nausea, fatigue and consequentially improves the QoL 13,[15][16][17][18][19][20][21][22][23] . Nevertheless, no ideal procedure or specific guidelines for the treatment of CP are available, and the decision on the use of specific surgical procedure drainage, re ection, drainage and re ection, denervation… i complicated [17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%